Materials of solid oxide electrolysis cells for H2O and CO2 electrolysis: A review - Peng Qiu; Cheng Li; Bo Liu; Dong Yan; Jian Li; Lichao Jia (Journal of Advanced Ceramics, 2023)
Reliable and economical energy storage technologies are urgently required to ensure sustainable energy supply. Hydrogen (H2) is an energy carrier that can be produced environment-friendly by renewable power to split water (H2O) via electrochemical cells. By this way, electric energy is stored as chemical energy of H2, and the storage can be large-scale and economical. Among the electrochemical technologies for H2O electrolysis, solid oxide electrolysis cells (SOECs) operated at temperatures above 500 ℃ have the benefits of high energy conversion efficiency and economic feasibility. In addition to the H2O electrolysis, SOECs can also be employed for CO2 electrolysis and H2O–CO2 co-electrolysis to produce value-added chemicals of great economic and environmental significance. However, the SOEC technology is not yet fully ready for commercial deployment because of material limitations of the key components, such as electrolytes, air electrodes, and fuel electrodes. As is well known, the reactions in SOEC are, in principle, inverse to the reactions in solid oxide fuel cells (SOFCs). Component materials of SOECs are currently adopted from SOFC materials. However, their performance stability issues are evident, and need to be overcome by materials development in line with the unique requirements of the SOEC materials. Key topics discussed in this review include SOEC critical materials and their optimization, material degradation and its safeguards, future research directions, and commercialization challenges, from both traditional oxygen ion (O2−)-conducting SOEC (O-SOEC) and proton (H+)-conducting SOEC (H-SOEC) perspectives. It is worth to believe that H2O or/and CO2 electrolysis by SOECs provides a viable solution for future energy storage and conversion.